Comparative analysis of two hydrogel architectures synthesized by gamma radiation based on dimethylacrylamide and acrylic acid grafted on polyethylene. (May 2022) - Valencia-May, E.G.; Rivera, E.; Novelo-Peralta, O.; Burillo, G.
Abstract: This study reports the synthesis of new modified polymeric systems that could be applied to the upload and delivery of drugs using gamma radiation. It is known that different architectures with the same components results in different properties, and it is therefore of interest to compare them. Two different systems were prepared using a polyethylene (PE) matrix grafted with a comb-type hydrogel based on N, N-dimethylacrylamide (DMAAm) and acrylic acid (AAc) and one interpenetrating network of the same monomers. First, PE was grafted onto DMAAm using gamma radiation under different reaction conditions, which involved changes in the absorbed dose, solvents, and concentration. Second, a crosslinked hydrogel network of DMAAm grafted onto a PE film surface was obtained by gamma radiation and subsequently modified with AAc to form two different architectures: a comb-type graft [PE- g -( net -DMAAm)]- comb -AAc and an interpenetrating network grafted onto PE, PE- g -[( net -DMAAm)- inter -( net -AAc)]. To evaluate the effect of the grafting reaction on the hydrophilicity, swelling studies were performed and the critical pH values were determined. The obtained systems were characterized by Fourier-transform infrared spectroscopy (FTIR), X-ray Diffraction (XRD), Differential scanning calorimetry (DSC), Thermogravimetric analysis (TGA), mechanical properties, and Scanning Electron Microscopy (SEM). Comparison between the properties of both systems was done. Highlights: A comparison between two architectures of grafted hydrogels based on AAc and DMAAm onto PE was done. IPN system presents more speed response and lower pH sensitivity that the comb-type system. A new systems of IPN and comb type Hydrogels grafted onto PE was synthesized.